ANALISIS SIX SIGMA UNTUK MENINGKATKAN KUALITAS PRODUK INDUSTRI KABEL - Fachrur, Aditya Rahadian; Ummi, Nurul; Ikrima, Qonitati (Teknik Industri Unikom, 2024)
Product quality plays an important role in the cable industry to meet standards and improve customer satisfaction, but product nonconformity is still an obstacle that affects production efficiency and costs. This study applies the Six sigma method with the DMAIC approach to the Improve stage to identify the causes of nonconformity and provide recommendations for improvement. The results of the study show four categories of Critical to Quality (CTQ) in cable products, with visual nonconformity as the most dominant at 423.167 km. The U control chart analysis shows that the variation of nonconformity per unit is still outside the statistical control limits, indicating that the production process is not yet stable, with a sigma level of 3.982, indicating significant opportunities for improvement. Based on the Pareto analysis, visual nonconformity is the main priority with the main causes coming from man, machine, method, material, and environmental factors. Recommendations for improvement include increased supervision, periodic machine maintenance, and operator training. Implementation of continuous improvement is expected to reduce nonconformity and improve the quality and efficiency of cable production.